2019
DOI: 10.1186/s13049-019-0621-7
|View full text |Cite
|
Sign up to set email alerts
|

Availability of suPAR in emergency departments may improve risk stratification: a secondary analysis of the TRIAGE III trial

Abstract: Introduction Soluble urokinase plasminogen activator receptor (suPAR) is a prognostic and nonspecific biomarker associated with short-term mortality in emergency department (ED) patients. Therefore, the blood level of suPAR might be usable for identification of patients at high- and low risk, shortly after arrival at the ED. Here, we investigate the value of adding suPAR to triage and how this may impact on risk stratification regarding mortality. Methods The analyses w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 18 publications
2
16
0
5
Order By: Relevance
“…They were also found to be immune mediators for developing acute and chronic kidney disease, and more recently predictive of in-hospital acute kidney injury and the need for dialysis in COVID-19 hospitalised patients ( Azam et al, 2020 , Hayek et al, 2020 , Hayek et al, 2015 ). A potential role for suPAR in triaging patients attending emergency departments has been highlighted ( Schultz et al, 2019 , Uusitalo-Seppälä et al, 2012 ). It is essential to emphasise that suPAR levels do not only reflect underlying infections but are also influenced by pre-existing comorbidities like diabetes mellitus, chronic inflammation and others.…”
Section: Discussionmentioning
confidence: 99%
“…They were also found to be immune mediators for developing acute and chronic kidney disease, and more recently predictive of in-hospital acute kidney injury and the need for dialysis in COVID-19 hospitalised patients ( Azam et al, 2020 , Hayek et al, 2020 , Hayek et al, 2015 ). A potential role for suPAR in triaging patients attending emergency departments has been highlighted ( Schultz et al, 2019 , Uusitalo-Seppälä et al, 2012 ). It is essential to emphasise that suPAR levels do not only reflect underlying infections but are also influenced by pre-existing comorbidities like diabetes mellitus, chronic inflammation and others.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that suPAR outperformed standard emergency triage in predicting mortality in ED patients, and the combination of triage and suPAR >5.7 ng/L (equivalent to the fourth suPAR quartile in the present study) yielded an AUC of 0.87 (0.82-0.93). 32 This suggests that suPAR indeed is a viable clinical marker for all-cause mortality in acutely admitted patients with COPD.…”
Section: Discussionmentioning
confidence: 99%
“…Positive and negative likelihood ratios as well as positive predictive values (PPV) and negative predictive values (NPV) were calculated from 2 × 2 contingency tables (crosstabulation) based on the diagnostic test and the outcome for the biomarkers. Before analysis cut-off, values for suPAR were defined as ≥3, ≥6, and ≥ 9 ng/ml based on [ 32 , 33 ] The cut-off for lactate was defined as ≥2.3 mmol/l based on the reference standard from Karolinska University Laboratory in Stockholm, Sweden. All statistical analysis was performed using IBM SPSS Statistics for Windows, version 25 (IBM Corp. Armonk, New York, USA).…”
Section: Methodsmentioning
confidence: 99%